Health status, resources, and job demands in geriatric nursing staff: A cross-sectional study on determinants and relationships - Korbus, Heide; Hildebrand, Claudia; Schott, Nadja; Bischoff, Laura; Otto, Ann Kathrin; Jöllenbeck, Thomas; Schöne, Daniel; Voelcker-Rehage, Claudia; Vogt, Lutz; Weigelt, Matthias; Wollesen, Bettina (International Journal of Nursing Studies, 2023)
Background: According to current estimates, the number of people needing care will double in the next 40 years. It is expected that between 130,000 and 190,000 additional nurses will be needed by 2030 in Germany. Physical and psychological burdens associated with nursing in long-term care facilities can develop into serious health risk factors and significantly impact occupational factors such as absenteeism, especially when linked to difficult working conditions. However, demands and resources specific to the nursing profession have not been analyzed extensively to preserve and promote nurses' workability and health adequately. Objective: Our study aimed to examine the extent to which perceived health among geriatric nursing staff in Germany is predicted by personal resources, job demands, and job resources. In addition, we analyzed the impact of different behavior and experience patterns on these relationships. Design, setting, and participants: An observational study was conducted between August 2018 and February 2020 in 48 nursing home facilities with 854 staff members in Germany as part of the project ‘PROCARE – Prevention and occupational health in long-term care’. Methods: The survey contained instruments that measure workplace exposure, musculoskeletal complaints, physical and mental well-being, chronic stress, and work-related behavior and experience patterns. In addition, health-related information on physical activity and nutrition was collected. Data were analyzed using structural equation modeling. Results: The combined physical and mental workload for geriatric nurses is very high, with 75 % showing chronic stress. In the overall model, job and personal resources have a stronger association with mental health than physical health, while job demands have an equal impact on mental and physical health. Coping behavior also plays an important key role that should be assessed and considered. A behavior and experience risk pattern (health-endangering) is more strongly associated with a lower health status than a health-promoting behavior pattern. Results of the multigroup test showed that work-related behavior and experience patterns significantly moderate the relationship between physical health and mental health (χ2 = 392/p ≤.001/df = 256/RMSEA = 0.028/CFI = 0.958/TLI = 0.931). Only 43 % show a health-friendly coping pattern. Conclusions: Our findings underline the importance of holistic health promotion, which not only aims at changes at the behavioral level and the development of coping strategies but also takes on the task of reducing the workload and including measures to improve the working climate. Trial registration number: DRKS.de (DRKS00015241); August 9, 2018. Tweetable abstract: Healthier coping patterns can benefit geriatric nurses' health. However, this is not a substitute for improving working conditions.
CRIS-Team Scopus Importer:2023-06-23
Keywords: Coping behavior; Health management; Inpatient care facility; Longterm care; Nursing homes; Occupational stress; Structural equation modeling